Kontrowersje i ponadczasowy wydźwięk legendy "Rokoszu Gliniańskiego" w sarmackiej wizji dziejów Augustyna Kołudzkiego = Controversy and persistence of the legend of the "Rokosz Gliniański" gentry rebellion in Augustyn Kołudzki's gentry-centred account - Buczek, Robert (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Historiographer Augustyn Kołudzki, living in the late 17th and early 18th centuries, has long fallen into obscurity: rarely is his name now mentioned in scientific papers. Yet, it was not so until mid-19th century, due to his "discovery" of the legend of the 'rokosz gliniański' gentry rebellion. The term 'rokosz gliniański' can be found in history books and describes the events of 1537 that took place near Gliniany - and as such is known to many. How surprising, then, must it have been to Kołudzkis contemporaries when he "discovered" an unknown episode in the Polish history, specifically - the times of king Ludwik of Hungary, and included it among the true events in his history of Poland, giving it a telling title: "The ancestral throne or the palace of eternity in a brief compilation of descriptions of Polish kings, dukes, and rulers by various recognised authors, from the first Lestko to the present times - a complete history of lives and memorable deeds", first issued in Poznań in 1707. According to Kołudzki, the king elect, in collusion with certain Polish aristocrats, intended to detach Ruthenia from Poland and annex it to Hungary. However, the plan fell through due to the dramatic rebellion staged by the gentry who foiled the plot by the king and senators, and who, as a result, made Ludwik grant them a variety of freedoms they since enjoyed. Kołudzki's conviction about the veracity of that event was so deep that he did not bother to review it critically. It was obvious, then, that he was in for a barrage of scathing critiques, reproaching him for a credulous approach to traditional legends and questioning the authenticity of the story. This author presents the controversy over Koludzki's account of the event and tries to nail the driving force behind the longevity of this legend which, for over a century, drew attention of the renowned 18th- and 19th-century authors, thus catalysing the creation of a number of valuable publications that set out to track down the story,s historical merits.
Keywords: czasopismo akademickie; polityka; kultura; czasopismo